2010
DOI: 10.1186/1471-2172-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Subolesin expression in response to pathogen infection in ticks

Abstract: BackgroundTicks (Acari: Ixodidae) are vectors of pathogens worldwide that cause diseases in humans and animals. Ticks and pathogens have co-evolved molecular mechanisms that contribute to their mutual development and survival. Subolesin was discovered as a tick protective antigen and was subsequently shown to be similar in structure and function to akirins, an evolutionarily conserved group of proteins in insects and vertebrates that controls NF-kB-dependent and independent expression of innate immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 36 publications
(68 reference statements)
1
35
0
1
Order By: Relevance
“…Subolesin knockdown resulted in higher A. phagocytophilum infection levels in ISE6 tick cells, supporting its role in the tick immune response. However, in tick guts and salivary glands, subolesin knockdown did not affect pathogen infection levels, probably due to the role of subolesin in tissue structure and development, which are required for pathogen infection (16,25,62), pointing to differences between in vitro and in vivo studies (12,21,60).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subolesin knockdown resulted in higher A. phagocytophilum infection levels in ISE6 tick cells, supporting its role in the tick immune response. However, in tick guts and salivary glands, subolesin knockdown did not affect pathogen infection levels, probably due to the role of subolesin in tissue structure and development, which are required for pathogen infection (16,25,62), pointing to differences between in vitro and in vivo studies (12,21,60).…”
Section: Discussionmentioning
confidence: 99%
“…Subolesin is a candidate tick protective antigen discovered in I. scapularis and subsequently found to be conserved in many tick species and other eukaryotes, where it is the ortholog of insect and mammalian akirins (14,(55)(56)(57)(58). Subolesin expression is induced in response to pathogen infection in ticks and plays an important role in the tick immune response to pathogen infection through the regulation of genes involved in innate immunity (14,16,56,59). As in previous experiments, subolesin mRNA levels did not change in response to A. phagocytophilum infection of ISE6 tick cells but increased in tick guts and salivary glands (12,60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subolesin, a tick homologue of the mammalian akarin family of proteins, is associated with the upregulation of innate immunity in various tick species (Zivkovic et al, 2010) and is proposed to be a transcription factor involved in multiple cellular processes (De la Fuente et al, 2008). Harrington et al (2009) showed that immunization of chickens with recombinant Aedes albopictus subolesin increased fed PRM mortality by 31% compared to control groups, suggesting that a potential PRM subolesin orthologue may be a target for control.…”
Section: Alternative and Novel Targetsmentioning
confidence: 99%
“…RNA interference of the subolesin gene in ticks has shown varying efficacy in terms of how well ticks are able to control bacterial infections. Zivkovic et al (2010) demonstrated that RNAi knock-down of subolesin in ticks increased infection by Francisella tularensis but decreased infection by Anaplasma marginale. Whether by means of immunological repression resulting in increased bacteria loads or by affecting other PRM systems, subolesin would make an interesting target for further vaccine studies against PRM.…”
Section: Alternative and Novel Targetsmentioning
confidence: 99%